2017
DOI: 10.37134/jrpptte.vol7.no2.4.2017
|View full text |Cite
|
Sign up to set email alerts
|

The character of teaching practices in a teacher education institution: Findings from observation checklist

Abstract: This study was conducted to characterise the teaching practices in a teacher education institution so as to inform us the existing practices which could then be compared with the aspired practices, uncovering the pedagogical shortfall. This study employed a form of implementation study using classroom observation. A total of 20 lessons drawn from Early Childhood Education, Mathematics, Science, Secondary School TESL (Teaching of English as a Second Language), History, Physical and Health Education, and Moral E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…It is conducted by giving a paper to participants which contains questions consisted about the application of conventional teaching methods and modern teaching methods used by one practitioner teacher. The observation in the form of the checklist is equally valid in evaluative research to determine the extent to which certain behaviours or teaching practices are observed throughout a lesson (Ong, Rahman, Wahid, Tajudin, Yahya, Mazuwai and Kosni, 2017). The student observation checklist is filled by ten students which giving a sign of checklist (√).…”
Section: Methodsmentioning
confidence: 99%
“…It is conducted by giving a paper to participants which contains questions consisted about the application of conventional teaching methods and modern teaching methods used by one practitioner teacher. The observation in the form of the checklist is equally valid in evaluative research to determine the extent to which certain behaviours or teaching practices are observed throughout a lesson (Ong, Rahman, Wahid, Tajudin, Yahya, Mazuwai and Kosni, 2017). The student observation checklist is filled by ten students which giving a sign of checklist (√).…”
Section: Methodsmentioning
confidence: 99%
“…Teaching preparation posits readiness of the Asatidz in handling ALIVE classes through the different strategies and methods of teaching and learning. There is a crucial need to capacitate teachers with pedagogical training as according to Ong et al, (2017), this will eventually impact the instruction of quality students.…”
Section: Teacher Equipped With Pedagogical Practicesmentioning
confidence: 99%
“…Closer to the context of this study, studies conducted in Malaysia have revealed the weak level of reflection among PSTs, where the reflections were found to be at the surface level. This occurs in both public universities and Institute of Teacher Education where most teacher education programmes are conducted (Ong et al, 2017;Ong et al, 2018;Yaacob et al, 2014). PSTs were found to be unable to reflect critically and propose solutions to problems.…”
Section: Reflective Practice Of Pre-service Teachers In Malaysiamentioning
confidence: 99%
“…As they are relatively new to the practice of teaching, their limited knowledge of and exposure to development of teaching methodology hinder them from truly reflecting on their teaching performance (Andreotti, 2006;Bryan et al, 2009;Krishnan & Yunus, 2017). Past research has also indicated shortcomings of the teacher education programmes in creating conducive learning environment for the development of critical reflection (Lim et al, 2016;Ong et al, 2017). Therefore, it is pivotal for PSTs to develop the ability to engage in reflective practice independently as a means for them to develop themselves professionally as competent teachers.…”
Section: Reflective Practice Of Pre-service Teachers In Malaysiamentioning
confidence: 99%